Model Pemberdayaan Masyarakat melalui Sistem Pemilahan Sampah Plastik Terpadu di Desa Margaharja - Adila Awaludin; Rizki Nugraha; Dewa Putra Sandang; Rahma Nazala Mutiara; Dwiguna Khoirul Anam; Salsabila Herdiani (Universitas Perjuangan Tasikmalaya, 2026)
Non-biodegradable plastic waste is a primary environmental problem at the household level, often ending up littering the environment and polluting rivers due to the lack of an effective waste separation system. This program aimed to provide dedicated plastic waste facilities in every hamlet, while also educating the community on the importance of sorting waste at the source to reduce environmental pollution. The implementation method involved the manufacture and distribution of simple and durable plastic waste bins to every hamlet, complemented by active socialization to residents on waste separation procedures and the potential economic value of the collected plastic waste. A total of 5 waste bins were successfully distributed. The visible impacts include a cleaner village environment, increased resident awareness in waste sorting, and the accumulation of plastic waste ready to be recycled or sold, opening up new economic opportunities. This plastic waste bin program has proven to be a practical and sustainable step. It not only directly addresses the cleanliness issue but also builds the foundation for an integrated waste management system that empowers the community economically and environmentally.